Cognitive Dysfunction and Mortality After Carotid Endarterectomy - Relander, Kristiina; Hietanen, Marja; Nuotio, Krista; Ijäs, Petra; Tikkala, Irene; Saimanen, Eija; Lindsberg, Perttu J.; Soinne, Lauri (Frontiers in Neurology, 2021)
Background: Carotid endarterectomy (CEA) has been associated with both postoperative cognitive dysfunction (POCD) and improvement (POCI). However, the prognostic significance of postoperative cognitive changes related to CEA is largely unknown. The aim of this study was to examine the associations between postoperative cognitive changes after CEA and long-term survival. Methods: We studied 43 patients one day before CEA as well as four days and three months after surgery with an extensive neuropsychological test array, and followed them for up to 14 years. POCD and POCI relative to baseline were determined with the reliable change index derived from 17 healthy controls. Associations between POCD/POCI and mortality within the patient group were studied with Cox regression analyses adjusted for confounders. Results: POCD in any functional domain was evident in 28% of patients four days after surgery and in 33% of patients three months after surgery. POCI was shown in 23% of patients at four days and in 44% of patients at three months. POCD at three months was associated with higher long-term mortality (hazard ratio 5.0, 95% CI 1.8-13.9, p=0.002) compared with patients with no cognitive decline. Conclusions: Our findings suggest that POCD in a stable phase, three months after CEA predicts premature death. Evaluation of postoperative cognitive changes is essential, and POCD in a stable phase after CEA should prompt scrutiny of underlying factors and better adherence to therapies to prevent recurrences and to promote early intervention in imminent deterioration.